Financial Literacy on Millenial Entrepeneurs during Pandemic Covid-19 - Firmialy, Sita Deliyana; Hidayat, Agus Maolana (International Research Journal of Business Studies, 2022)
As one of the drivers of economic success and societal welfare in Indonesia, financial literacy is a must for young entrepreneurs today. The study attemps to evaluate Millenial entrepreneurs financial literacy and financial well-being conditions while several PPKM (Restrictions on Community Activities) during Pandemic Covid-19 are in effect. Between mid-October 2021 and early January 2022, the survey used 100 young entrepreneurs aged 21-40 in West Java Province, Indonesia as samples. The hypotheses testing results from Exploratory Factor Analysis (EFA) and Structural Equation Model (SEM) methods show a consistent association between the main components of financial literacy with the level of financial well-being, with insurance and personal savings and loans becoming the dominant predictor affected financial knowledge, followed with security that serves as main determinant that affected the level of financial attitude of these millenial entrepreneurs. However, this study has limitation as the sample and number of experimental parameters are small.